Air quality assessment in urban areas of Gipuzkoa (Spain) Evaluación de la calidad del aire en medios urbanos de Gipuzkoa - Aitana Lertxundi; Maria Dolores Martinez; Mikel Ayerdi; Jon Álvarez; Jesús María Ibarluzea (Elsevier, 2010)
Objectives: To evaluate the air quality to which a population of 90,000 inhabitants in the province of Gipuzkoa (Basque Country, Spain) is exposed. The population resides in a periurban environment, where industrial activity (11 iron and steel foundries) is scattered among residential areas. Methods: Throughout 2006 and 2007, levels of particulate matter less than 2.5mm in diameter (PM2.5) were quantified and levels of trace elements in PM2.5 fraction [cadmium (Cd), arsenic (As), manganese (Mn), copper (Cu), chromium (Cr), nickel (Ni), iron (Fe), lead (Pb), mercury (Hg) and zinc (Zn)] were analyzed. The samples were gathered in seven sampling sites using three high-volume Digitel DAH 80 samplers. Annual and seasonal variability were evaluated for the various contaminants in each valley and PM10 and PM2.5 samples were also gathered at the same site for a month, with the goal of analyzing the composition of trace elements in each particle size. Finally, the results were compared with those obtained from the same study area by the Basque Government Air Quality Network equipment. Results: The observed PM2.5 concentrations (12.2-28.9mug/m³) were similar to those described in urban environments in large European cities, while mean trace element concentrations were significantly higher. The Mn levels observed in all three valleys indicated the influence of the steel and metal industries on air quality. Conclusion: The finding that levels of particulate matter and trace elements in the study area were similar to or higher than those found in metropolitan areas has implications for the evaluation of health risks in populations far from large population centers. Objetivo: El objetivo del estudio es evaluar la calidad del aire a la que está expuesta una población de 90.000 habitantes de Gipuzkoa que residen en un entorno periurbano, donde las actividades industriales (11 industrias siderometalúrgicas) se entremezclan con zonas residenciales en la propia trama urbana. Métodos: Se cuantificaron las concentraciones de partículas de 2,5mm de diámetro (PM2.5) y se analizaron los elementos traza asociados a PM2.5: cadmio (Cd), arsénico (As), manganeso (Mn), cobre (Cu), cromo (Cr), níquel (Ni), hierro (Fe), plomo (Pb), mercurio (Hg) y zinc (Zn) a lo largo de 2006 y 2007. Las muestras se recogieron a partir de 3 captadores de alto volumen DIGITEL Modelo DAH 80 en 7 puntos de muestreo. Se analizó la variabilidad anual así como la variabilidad estacional de los diferentes contaminantes en cada valle. Asimismo, se recogieron muestras de PM10 y PM2.5 con equipos similares durante un mes y en el mismo sitio para analizar la composición de los elementos traza en las diferentes fracciones PM10 y PM2.5. Por último, los resultados fueron comparados con los de los equipos de la Red de Calidad del Aire del Gobierno Vasco ubicados en la misma área de estudio. Resultados: Las concentraciones de PM2.5 observadas (12.2-28.9myg/m³) fueron similares a las descritas en entornos urbanos de grandes ciudades europeas. Las concentraciones medias de elementos traza, en cambio, superaron con gran diferencia a las de las ciudades europeas. Las concentraciones de Mn encontradas en los tres valles indican la influencia de la industria siderometalúrgica en la calidad del aire. Conclusión: Los resultados de partículas y elementos traza encontrados en el área de estudio presentan valores similares o superiores a las áreas metropolitanas, lo cual tiene implicaciones en la valoración del riesgo en la salud de entornos apartados de los grandes núcleos de población.